De studie van Imre Forró in de jaren 30 aan de Utrechtse universiteit - Bozzay, Réka (Acta Neerlandica, 2024)
Imre Forró, a theology student from Debrecen, studied at Utrecht University in the 1930s with a scholarship from the Stipendium Bernardinum. Several sources about his studies abroad have survived. Some of them are kept in the archives of the Reformed Church District of Tiszántúl, others are in the family archives. The sources allow us to reconstruct the life of the former student abroad. We know with which professor he studied and took his exams, where he lived, with whom he made friends, which associations (International Students’ Club, Voetius Reformed Theologians’ Association) he was a member of. Forró was the first to start a systematic, source-level investigation of the Franeker peregrination, but (due to illness and unfounded accusations of plagiarism) he was only able to continue this after his retirement.